PELATIHAN PEMANFAATAN AKUN BELAJAR.ID DALAM PEMBUATAN BAHAN AJAR BERBASIS GOOGLE SITES BAGI GURU SILN DI SINGAPURA - Fitria, Rezki; Ainur Rifqi,; Ayu Wulandari,; Muhammad Sholeh,; Rofiqoh Mardhiana,; Isaura Nur Havidah,; Agiska Maya Saputri, (DEDICATE: Journal of Community Engagement in Education, 2024)
Work scientific Devotion to this Community (PkM). For give enhancement understanding and skills of SILN teachers in Singapore make teaching materials using Google Sites. Method used in PkM This with use approach coaching. Participant (teacher) training will accompanied by a coach or expert guide? in field material presented? about utilization learn.id account in make based teaching materials google sites. Strengthening material training consisting? from: (1) preparation draft differentiated teaching materials; (2) manufacturing teaching materials based on Google sites. In terms of here, team from the Faculty of Education Management Study Program Surabaya State University of Educational Sciences (UNESA) will give contribution optimally through? activity training with target activity is a teacher at the level education The base is at SILN Singapore. Training results This showing that enhancement teacher's abilities in understand differentiation learning and application based teaching materials google sites For support regulations government in acceleration optimization learn.id account.